ENTREPRENEURSHIP TREND AND THE EFFECT OF MARKET FOCUS ON PERFORMANCE (Third Sector Social Economic Review, 2020)
This study aims to investigate and reveal whether entrepreneurship tendency and market focus have an impact on business performance. While examining the effect of entrepreneurship tendency and market focus on business performance, we focused on the market and financial performance indicators as a proxy of business performance. The selected target population of the research is the managers of enterprises from Turkistan Province. A total of 81 questionnaire forms were distributed to participants. Of those, 71 came back. Thus, the return rate of the surveys is 87.65%. All of the variables used in the questionnaire are measured with a 5-point Likert type scale. The research consists of 32 questions. The analysis of the data included the frequency tables of the demographic characteristics of the respondents, factor analysis, reliability tests, correlation analysis, and the test hypotheses including the mean and standard deviations of the variables.
Keywords: Entrepreneur; Entrepreneurship; Entrepreneurship Tendency; Market Focus; Business Performance; Market Performance; Financial Performance